Turkish-American Commercial Relations (1908-1930): The Success of Trade-The Failure of Investment - Karakoç, Ercan; Küçük, Hasan (Journal of History Culture and Art Research, 2020)
Commerce had a prominent role in the Ottoman and later Turkish-American relations. The first agreements the American administration signed with Ottoman authorities in the late 18th century were aimed at assuring the safe passage of the US merchant ships through North Africa. After this initial acquaintance, a new era of Ottoman-American relations was established in 1830 when the US government concluded a trade and navigation treaty with the Ottoman government in İstanbul, resulting in the expansion of American activities in the region. During this time, the US generally ranked as the second-largest consumer of Ottoman exports, whereas American products dominated the Ottoman market during the Armistice Period. Despite the robust trade exchange between the two states, however, their commercial relationship was oft overshadowed by the era’s political and diplomatic tensions and the imperialist rivalry of the European powers prevented the US from making sizable and lasting investments in the region. This article, therefore, aims to analyze the commercial relations of these two countries and to present the reasons why bilateral trade did not end up in investments from the restoration of the Ottoman Constitution in 1908 until the inauguration of statist economic policies of Turkey in 1930. The study has made use of the American archives and foreign trade records as well as benefitted from Levant Trade Review, a publication of the American Chamber of Commerce for the Levant in İstanbul.